Ambientes invalidantes, conductas basadas en valores y salud mental: Un modelo explicativo basado en perspectivas de intervención conductuales-contextuales: Invalidating environments, values-based behaviors, and mental health: An explanatory model based on contextual-behavioral intervention perspectives - Amau-Rios, Eliane Nicoll; Jara-Chuquihuara, Maria Alexandra; Ospina-Valencia, Sissy; Sifuentes-Villanueva, Brenda; Tintaya-Pelaes, María Elena; Velasquez-Huiza, Mariana; Okumura-Clark, Alvaro (Revista de Psicopatología y Psicología Clínica, 2025)
ABSTRACT Objective: To examine the mediating role of value-based behaviors in the relationship between invalidating environments, both past and present, and mental health indicators. Method: A total of 546 Peruvian adults participated in the study, ranged in age from 18 to 67 years (53.3% were females). Structural equation models were employed to test the hypothesized mediation models. Results: The findings indicate that both progress toward and obstruction of a meaningful life mediate the relationship between certain types of invalidation (stemming from the current context and paternal invalidation during childhood) and mental health indicators. However, this dynamic was not observed in the case of maternal invalidation during childhood. Conclusions: These results are discussed in consideration of theoretical frameworks based on behavioral-contextual interventions, as well as sociocultural perspectives relevant to the research. Additionally, the limitations related to sampling and the implications of the preliminary proposals presented are thoroughly analyzed. RESUMEN Objetivo: Examinar el rol mediacional de las conductas basadas en valores entre ambientes invalidantes, tanto pasados como presentes, e indicadores de salud mental. Método: Participaron 546 adultos peruanos, con un rango de edad entre 18 y 67 años (el 53.3% eran mujeres). Se emplearon modelos de ecuaciones estructurales para probar los modelos de mediación hipotetizados. Resultados: Los hallazgos indican que tanto el progreso como la obstrucción hacia una vida valiosa median la relación entre ciertos tipos de invalidación (proveniente del contexto actual y de la figura paterna durante la infancia) e indicadores de salud mental. Sin embargo, esta dinámica no se observó en el caso de la invalidación maternal infantil. Conclusiones: Se discuten estos resultados tomando en cuenta marcos teóricos basados en intervenciones conductuales-contextuales, además de perspectivas socioculturales relevantes para la investigación. Se analizan en profundidad las limitaciones sobre el muestreo y las implicaciones de propuestas preliminares realizadas.